Spray solution volumes to control Brevipalpus yothersi mite in successive applications and impact on citrus fruit drop with leprosis symptoms - DE Castro, Matheus cardoso [UNESP]; Yamane, Danilo ricardo; Bassanezi, Renato beozzo; Franco, Danilo; Fukuda, Leandro aparecido; Ferreira, Marcelo Da Costa; De Andrade, Daniel Junior [UNESP] (Systematic & Applied Acarology Soc London, Natural History Museum, 2024)
Citrus leprosis mite [ Brevipalpus yothersi Baker (Acari: Tenuipalpidae)] is traditionally controlled with acaricide applications using a high volume of spray solution (> 2000 L.ha(-1)). However, high spray solution volumes can generate water waste and environmental contamination. An experiment was set up in a sweet orange orchard located in the municipality of Taquaral, Sao Paulo, Brazil, aiming to optimize the spray solution volume required for more efficient control of the leprosis mite. The experiment was conducted from December 2020 to July 2022. Two spray solution volumes were evaluated: 100 and 180 mL m(-3) of plant canopy. In total, seven acaricide applications were performed. During the experiment, we assessed the incidence and infestation of the leprosis mite. Additionally, at the end of the experiment, we counted the number of plants and fallen fruits exhibiting leprosis symptoms. The treatment with a spray volume of 180 mL m(-3) was more effective in controlling mites, as the incidence and infestation of B. yothersi were lower in this treatment. Moreover, this treatment resulted in fewer plants with fallen fruits and a reduced number of fallen fruits showing leprosis symptoms.
Keywords: Application technology; Citrus sinensis; Citrus leprosis mite; Acaricides